2022
DOI: 10.3389/fpsyg.2022.788712
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Emotion on Driving Decisions at Different Risk Levels: An Eye Movement Study

Abstract: To explore the influences of traffic-related negative emotions on driving decisions, we induced drivers’ three emotions (neutral emotion, traffic-related negative emotion, and traffic-unrelated negative emotion) by videos, then the drivers were shown traffic pictures at different risk levels and made decisions about whether to slow down, while their eye movements were recorded. We found that traffic-related negative emotion influenced driving decisions. Compared with neutral emotion, traffic-related negative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In accordance with this, Kovácsová et al (2016) and Zimasa et al (2017) found that while negative emotions might potentially influence driving behavior, the effect on aggressive driving behavior was not always straightforward or predictable. Recent studies by Karras et al (2023) and Zhang et al (2022) supported this result by emphasizing that dysfunctional impulsivity and a lack of forgiveness had stronger correlations with aggressive driving behavior. These studies were carried out with a focus on exploring alternative factors influencing driving behavior beyond the traditionally impulsivity dimensions.…”
Section: Resultsmentioning
confidence: 78%
“…In accordance with this, Kovácsová et al (2016) and Zimasa et al (2017) found that while negative emotions might potentially influence driving behavior, the effect on aggressive driving behavior was not always straightforward or predictable. Recent studies by Karras et al (2023) and Zhang et al (2022) supported this result by emphasizing that dysfunctional impulsivity and a lack of forgiveness had stronger correlations with aggressive driving behavior. These studies were carried out with a focus on exploring alternative factors influencing driving behavior beyond the traditionally impulsivity dimensions.…”
Section: Resultsmentioning
confidence: 78%
“…Eye tracking technology is used in an ever-growing list of fields. In basic science research, the study of eye movements contributes to a comprehensive understanding of various facets of human brain function, such as vision [Gibaldi and Banks, 2019], vestibular processing [Cullen, 2023], [Otero-Millan and Kheradmand, 2016], attention [Kelley et al, 2008], motor learning [Sedaghat-Nejad and Shadmehr, 2021], and emotions [Zhang et al, 2022]. In clinical settings, eye tracking systems play a crucial role in medical diagnosis across various disciplines including neurology [Leigh and Zee, 2015], ophthalmology [Grillini et al, 2020], otology [Korda et al, 2021], psychology [Walker-Smith et al, 2013], and psychiatry [Takahashi et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, we can state the fact of a greater intensity of drivers' operator actions in Tyumen and traffic on the stretches of the city's road network at relatively higher speeds than in Novosibirsk. Analyzing this observation, the author came to the conclusion that Tyumen drivers try to use the high dynamics (intense acceleration, high speed) as a compensation for the loss of time during numerous and rather long downtimes while waiting for a permitting traffic signal at regulated intersections [70,71].…”
mentioning
confidence: 99%